2019
DOI: 10.1101/19007989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Personalized Multi-Component Lifestyle Intervention Program Leads to Improved Quality of Life in Persons with Chronic Kidney Disease

Abstract: Introduction: Lifestyle interventions have been shown to produce favorable changes in some health outcomes in patients with chronic kidney disease (CKD). However, few such studies, employing real world methods have been completed in patients with CKD. Objective: This study tested the effectiveness of a comprehensive, multicomponent, lifestyle intervention, delivered through individualized counseling on a variety of health outcomes in pre-dialysis CKD patients. Methods: Eligible patients were assigned randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Our results, along with other studies that showed the importance of physical activity for quality of life in HD patients, have significant value in designing the multicomponent lifestyle interventions involving physical exercise. This was confirmed by a novel study that showed that multi-component lifestyle intervention improved a variety of health outcomes in CKD patients [ 37 ]. Moreover, Mustata et al [ 38 ] showed that long-term exercise training improved HRQOL in patients on predialysis, while Ota et al [ 39 ] reported that a program including stretching and isotonic muscle conditioning improved components of daily living in elderly hemodialysis patients.…”
Section: Discussionmentioning
confidence: 77%
“…Our results, along with other studies that showed the importance of physical activity for quality of life in HD patients, have significant value in designing the multicomponent lifestyle interventions involving physical exercise. This was confirmed by a novel study that showed that multi-component lifestyle intervention improved a variety of health outcomes in CKD patients [ 37 ]. Moreover, Mustata et al [ 38 ] showed that long-term exercise training improved HRQOL in patients on predialysis, while Ota et al [ 39 ] reported that a program including stretching and isotonic muscle conditioning improved components of daily living in elderly hemodialysis patients.…”
Section: Discussionmentioning
confidence: 77%
“…Structured exercise or physical activity interventions in this population 3 , 4 , 5 have improved functional abilities, reversed sarcopenia, and enhanced health-related quality of life. 5 , 6 , 7 Despite significant resources devoted to increasing the rehabilitative outcomes of this vulnerable population, 8 considerable work remains to develop effective, sustainable, patient-centered strategies geared toward the preservation of functional status.…”
mentioning
confidence: 94%